Yuanhuatine from Daphne genkwa selectively induces mitochondrial apoptosis in estrogen receptor α-positive breast cancer cells in vitro - Zhang, Ying-Ying; Shang, Xin-Yue; Hou, Xue-Wen; Li, Ling-Zhi; Wang, Wei; Hayashi, Toshihiko; Zhang, Yan; Yao, Guo-Dong; Song, Shao-Jiang (Planta Medica, 2019)
Breast cancer is one of the most common cancers diagnosed among women worldwide. Estrogen receptor alpha (ERα) is a transcriptional factor that plays an important role in the development and progression of breast cancer. Yuanhuatine, a natural daphnane-type diterpenoid extracted from Daphne genkwa, was reported to exhibit significant cytotoxicity against breast cancer cells. However, the underlying mechanism is still unclear. In this study, we evaluated the cytotoxicity of yuanhuatine on two breast cancer cell lines that are ERα-positive and -negative. The results show that yuanhuatine inhibits the growth of ERα-positive cells (MCF-7) with much stronger inhibitory activity (IC50 = 0.62 µM) compared with positive control tamoxifen (IC50 = 14.43 µM). However, no obvious cytotoxicity was observed in ERα-negative cells (MDA-MB-231). Subsequent experiment also indicated that yuanhuatine markedly induced mitochondrial dysfunction, leading to apoptosis in MCF-7 cells. Molecular docking studies suggest the potential interactions between yuanhuatine and ERα. Immunofluorescence staining and Western blot analysis indicated that yuanhuatine down-regulated the expression of ERα in MCF-7 cells. MPP, a specific ERα inhibitor, significantly enhanced yuanhuatine-induced mitochondrial dysfunction and apoptosis in MCF-7 cells. On the contrary, the treatment with yuanhuatine causes no apoptosis in MM231 cells. Altogether, in vitro and in silico results suggested that ERα down-regulation was involved in yuanhuatine-induced mitochondrial dysfunction and apoptosis in ERα-positive breast cancer cells. Thus, yuanhuatine could be a potential candidate for treating ERα-positive breast cancer.
Keywords: Daphne genkwa; Thymelaeaceae; breast cancer; estrogen receptor α; apoptosis